Amazing schemes within your genes - Balkwill, Frances R.; Rolph, Mic (Minneapolis Carolrhoda Books, 1993)
Discusses the structure and function of genes, their adaptations and mutations, and basic genetic processes, particularly as they occur in humans.
Keywords: Genes -- Juvenile literature; Human genetics -- Juvenile literature; Genetics